Translocation of reindeer from South Georgia to the Falkland Islands - Bell, Cameron M.; Dieterich, Robert A. (Rangifer, 2010)
This report describes the first translocation of reindeer Rangifer tarandus from South Georgia to the Falkland Islands, in the South Atlantic Ocean. Reindeer were introduced from Norway to the subantarctic island of South Georgia on three occasions in the early 1900s by Norwegian whalers, and today they exist as two discrete herds, numbering approximately 2600 individuals in total. Because of concerns over the impact on native vegetation, the long-term eradication of reindeer from South Georgia has recently been proposed. A translocation of reindeer to the Falkland Islands was undertaken in 2001 by the Falkland Island Government with two objectives: (1) to preserve the genetic resources of at least one of the South Georgia herds; and (2) to facilitate the diversification of the agricultural sector of the Falkland Islands by establishing a commercial reindeer herd. Techniques developed and used in North America for the successful relocation of large numbers of calves were adopted for the translocation. A total of 59 calves (26 females and 33 males) were successfully translocated from South Georgia to the Falklands Islands in 2001, and subsequently produced their first offspring in 2003. Good husbandry practices and an understanding of biology and behaviour are essential for the successful translocation of reindeer. Flytting av rein fra Sør-Georgia til Falklandsøyene Abstract in Norwegian / Sammendrag: Artikkelen beskriver den første overføring av rein Rangifer tarandus fra Sør-Georgia til Falklandsøyene i søratlanteren. Tamrein fra Norge ble flyttet til den subarktiske øya Sør-Georgia ved tre anledninger i perioden 1911 til 1925 i forbindelse med den norske hvalfangsten der. I dag består bestanden av rundt regnet 2600 dyr fordelt på to geografisk atskilte flokker. Av hensyn til den naturlige vegetasjonen på øya er det forslag om å på sikt utrydde reinbestanden på øya. Regjeringen på Falklandsøyene foretok en første overføring av rein fra Sør-Georgia i 2001 ut fra en målsetting om å 1) bevare genetiske ressurser fra minst en av de to reinflokkene, og 2) øke mulighetene innenfor landbrukssektoren på Falklandsøyene ved å etablere en kommersiell reinflokk der. Overføringen ble utført med metoder som hadde vist seg formålstjenlige ved flytting og nylokalisering av kalver i Nord-Amerika. Totalt ble 59 kalver overført i 2001 derav 26 hunndyr. De overførte reinene produserte kalver i 2003. God driftspraksis og biologisk og atferdsmessig forståelse var viktig for en vellykket overføring.